Informality through sustainability : urban informality now - Di Raimo, Antonino, 1973-; Lehmann, Steffen, 1963-; Melis, Alessandro (New York : Routledge, 2021)
"Informality through Sustainability explores the phenomenon of informality within urban settlements and aims to unravel the subtle links between informal settlements and sustainability. Penetrating its global profile and considering urban informality through an understanding of local implications, the authors collectively reveal specific correlations between sites and their local inhabitants. The book opposes simplistic calls to legalise informal settlements or to view them as 'problems' to be solved. It comes at a time when common notions of 'informality' are being increasingly challenged. In 25 chapters, the book presents contributions from well-known scholars and practitioners whose theoretical or practical work addresses informality and sustainability at various levels, from city planning and urban design to public space and architectural education. Whilst previous studies on informal settlements have mainly focused on cases in developing countries, approaching the topic through social, cultural and material dimensions, the book explores the concept across a range of contexts, including former Communist countries and those in the so-called Global North. Contributions also explore understandings of informality at various scalar levels--region, precinct, neighbourhood and individual building. Thus, this work helps reposition informality as a relational concept at various scales of urbanisation. This book will be of great benefit to planners, architects, researchers and policymakers interested in the interplay between informality and sustainability"--
Includes bibliographical references and index.
Keywords: Squatter settlements; City planning -- Environmental aspects; Urban policy; Urban ecology (Sociology)